Postoperative Complications after Repair of Tibial Plateau Fractures - Choo, Kevin J.; Morshed, Saam (The Journal of Knee Surgery, 2014)
Tibial plateau fractures are common orthopedic injuries and represent a spectrum of injury severity defined by the fracture morphology and the associated soft tissue injury. The management of tibial plateau fractures is challenging, and patients are at risk for adverse outcomes including infection, malunion, nonunion, and stiffness. Accurate diagnosis and early management can mitigate the impact of these complications. When complications do occur, a principle-based approach outlined in this review can minimize the burden to patients in their return to function.
Keywords: tibial plateau fracture; complications; open reduction; internal fixation; postoperative infection